Interactions of Opioids and HIV Infection in the Pathogenesis of Chronic Pain - Liu, Bolong; Liu, Xin; Tang, Shao-Jun (Frontiers in Microbiology, 2016)
Over 50% of HIV-1/AIDS patients suffer chronic pain. Currently, opioids are the cornerstone medications for treating severe pain in these patients. Ironically, emerging clinical data indicates that repeated use of opiate pain medicines might in fact heighten the chronic pain states in HIV patients. Both laboratory-based and clinical studies strongly suggest that opioids exacerbate the detrimental effects of HIV-1 infection on the nervous system, both on neurons and glia. The combination of opioids and HIV-1infection may promote the damage of neurons, including those in the pain sensory and transmission pathway, by activating both caspase-dependent and caspase-independent pro-apoptotic pathways. In addition, the opiate-HIV-1 interaction may also cause widespread disturbance of glial function and elicit glial-derived pro-inflammatory responses that dysregulate neuronal function. The deregulation of neuron-glia cross-talk that occurs with the combination of HIV-1 and opioids appears to play an important role in the development of the pathological pain state. In this article, we wish to provide an overview of the potential molecular and cellular mechanisms by which opioids may interact with HIV-1 to cause neurological problems, especially in the context of HIV-associated pathological pain. Elucidating the underlying mechanisms will help researchers and clinicians to understand how chronic use of opioids for analgesia enhances HIV-associated pain. It will also assist in optimizing therapeutic approaches to prevent or minimize this significant side effect of opiate analgesics in pain management for HIV patients.